ANALISIS ARUS INRUSH SAAT SWITCHING KAPASITOR BANK PADA BUSBAR 2 (Suatu Studi DI PT.PLN (persero) GARDU INDUK GANDUL) - Irfan Hidayat; Nur Hanifah Yuninda; Imam Arif Raharjo (Journal of Electrical Vocational Education and Technology, 2019)
Irfan Hidayat, Analysis of Inrush Flow when Switching Bank Capacitors on Busbar 2. Thesis. Jakarta, Electrical Engineering Education Study Program, Faculty of Engineering, Jakarta State University 2018. Supervisor: Nur Hanifah Yuninda, ST., MT., And Imam Arif Raharjo, S.Pd., MT. This study aims to analyze the inrush current when switching bank capacitors. The inrush current can be defined as the magnitude of the current surge that first appears in the circuit, when the circuit is connected to the load. As with transient phenomena, inrush currents in electrical circuits are considered undesirable. In every electrical equipment there must be an inrush current. The inrush current is dangerous for the system when the peak value of the inrush current is very large. To reduce the value of inrush current using a series reactor. The research method used in this study is the experimental method using a research design with pre-experimental design used is one-group pretest-posttest design. In collecting data, the circuit inductance data is collected and on the bank capacitors. To analyze how much the inrush current and frequency before and after the addition of a series reactor. The results showed inrush current when switching capacitor banks before the addition of series reactors exceeded the IEEE Std C37.012-2005 standard where the inrush current is allowed 100 times the rms current. The value of the inrush current and frequency at each step before the addition of the series reactor is: step 1 = 16.29 kA, 4.16 kHz; Step 2 = 289.7 kA, 147.32 kHz; Step 3 = 349.22 kA, 133.2 kHz; Step 4 = 372.47 kA, 126.28 kHz; Step 5 = 386.03 kA, 122.7 kHz; Step 6 = 410.146 kA, 125.15 kHz. The value of the inrush current and frequency at each step after the addition of the series reactor is: step 1 = 1.1 kA, 0.2 kHz; Step 2 = 26.56 kA, 13.5 kHz; Step 3 = 30.68 kA, 11.7 kHz; Step 4 = 36.35 kA, 12.3 kHz; Step 5 = 41.08 kA, 13.05 kHz; Step 6 = 45.27 kA, 13.8 kHz. So that the inrush current is in accordance with the IEEE Std C37.012-2005 standard. ABSTRAK Irfan Hidayat, Analisis Arus Inrush saat Switching Kapasitor Bank pada Busbar 2. Skripsi. Jakarta, Program Studi Pendidikan Teknik Elektro Fakultas Teknik Universitas Negeri Jakarta 2018. Dosen Pembimbing: Nur Hanifah Yuninda, ST., MT., dan Imam Arif Raharjo, S.Pd., MT. Penelitian ini bertujuan untuk menganalisis arus inrush pada saat switching kapasitor bank. Arus inrush dapat didefinisikan sebagai besarnya lonjakan arus pertama kali muncul pada rangkaian, saat rangkaian terhubung dengan beban. Sama halnya dengan fenomena transien, arus inrush dalam rangkaian listrik dianggap sebagai hal yang tidak diinginkan. Pada setiap peralatan listrik pasti terjadi arus inrush. Arus inrush berbahaya bagi sistem ketika nilai puncak arus inrush terjadi sangat besar. Untuk mereduksi besar nilai arus inrush menggunakan reaktor seri. Metode penelitian yang digunakan pada penelitian ini adalah metode eksperimen menggunakan rancangan penelitian dengan desain pre-experimental yang digunakan adalah one-group pretest-posttest design. Pada pengumpulan data, dilakukan pengambilan data induktansi rangkaian dan pada kapasitor bank. Untuk menganalisis seberapa besar arus inrush dan frekuensi sebelum dan sesudah penambahan reaktor seri. Hasil penelitian menunjukan arus inrush saat switching kapasitor bank sebelum penambahan reaktor seri melebihi standart IEEE Std C37.012-2005 dimana arus inrush yang di ijinkan 100 kali arus rms. Besar nilai arus inrush dan frekuensi pada setiap step sebelum penambahan reaktor seri sebesar: step 1 = 16,29 kA, 4,16 kHz; Step 2 = 289,7 kA, 147,32 kHz; Step 3 = 349,22 kA, 133,2 kHz; Step 4 = 372,47 kA, 126,28 kHz; Step 5 = 386,03 kA, 122,7 kHz; Step 6 = 410,146 kA, 125,15 kHz. Besar nilai arus inrush dan frekuensi pada setiap step setelah penambahan reaktor seri sebesar: step 1 = 1,1 kA, 0,2 kHz; Step 2 = 26,56 kA, 13,5 kHz; Step 3 = 30,68 kA, 11,7 kHz; Step 4 = 36,35 kA, 12,3 kHz; Step 5 = 41,08 kA, 13,05 kHz; Step 6 = 45,27 kA, 13,8 kHz. Sehingga arus inrush sesuai dengan standart IEEE Std C37.012-2005.